A SURVEY TO OBSERVE THE COMMONLY USED TREATMENT PROTOCOL FOR TRIGEMINAL NEURALGIA BY PHYSIOTHERAPIST (International Journal of Physiotherapy, 2016)
Background: Trigeminal neuralgia (TN) is also known as prosoplasia it is also termed as a Suicidal disease or Fothergill disease. The neuropathic condition is characterized by recurrent episodes of facial pains which are triggered by touch, chewing and shaving. The pain initiates from the 5th cranial nerve which is known as trigeminal nerve. The objective of this study was to evaluate treatment protocol used by physiotherapist for trigeminal neuralgia patients.Methods: It was cross-sectional descriptive study in which data was collected from certified physiotherapists working in private/ government hospitals for more than 1 year in Karachi. The sample size was 60 and Purposive random sampling technique was used. The data collection procedure was questionnaire based that was filled by physiotherapists.Results: In this study 77% physiotherapist’s answered that physiotherapy is helpful in patients with T.N and, 23% said that it is not beneficial.13.3% patients reported that they were taking medicines other than steroid and analgesics like (carbamezipine, gabapentine), 50% were taking steroids, 33.3% were taking NSAIDs, and 3.3% were taking antibiotics. Regarding Modality prescribed by physiotherapists in Trigeminal Neuralgia 68% physiotherapists used TENS to treat the disease, 30% used electrical stimulation andonly 2% used ultrasound.Conclusions: Physiotherapy treatment is effective in the patients of T.N. Awareness needs to be generated amongst general public concern in the role of physiotherapy relating to the disease. The symptoms of some patients are not eased by the medicines, they should move toward electrical stimulation.